Legal Assurance of Investor Dispute Settlement with Indigenous Law Communities in Legal Pluralism Perspective - Susanto, Herman; Kristhy, Mutia Evi; Kristanto, Kiki (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
With the enactment of Law Number 11 of 2020 concerning Job Creation, it has become a positive turning point in the Government's efforts to increase the number and value of investment in Indonesia while at the same time responding to challenges according to current developments with the method of resolving investment disputes by prioritizing deliberation and consensus up to the court mechanism. The purpose of this legal research is to analyze the legal certainty regarding the settlement of disputes between investors and indigenous peoples and to analyze the policies taken by the Government and Regional Governments in the context of resolving disputes in the perspective of legal pluralism. The research method used in this research is the normative legal method. According to the author, this is needed in order to provide guarantees for the basis of legal certainty, namely legal certainty and strengthening as well as the presence of the State in providing policy directions, commitments and joint responsibilities of the Government, Regional Governments in supporting and carrying out the process of forming laws and regulations that are in harmony and balance so that ensure the existence of public law and order in providing legal certainty in investing for investors, the community and the Government as well as the Regional Government in the context of improving regional economic development and community welfare in a fair and equitable manner.